(3MGTjI Ydi Ndjd GdbRhjfj Ydi cJGH YOI GdCUhd ddTjN GdWhSjs - (3GdNdjdj, GdbRhjfj, CHh jYdi, Ndjd Hf YHO Gddg Hf CMeO Hf EHQGgje GHf GdNdjd, J (B446 (3g`s
(3ChdgG (B:s
.. (3gPG MO CUhd Gdabg HGYJHGQ eYfi GdEVGaj Gdefbhd Yfg hGdCUhd LeY CUd hgh eG jHJfj Ydjg GdTjA hGdbGYLI GdcdjI hGdOdjd hZjQ Pdc hEPG CVja Edi GdYdhe hGdeSGFd ceG ajeG fMf ajg aGdeJHGOQ efg YQaG GdOdjd (B...s
(3BNQgG (B:s
.. (3hGdJbOjQ cd eHGM YdI JQc GdMQGe Ch SHHg Ch fMh Pdc hGNJU GdJbOjQ Hg dXghQ YOe MJg EdG HNdGa GdKGfj hajS gPG GdGSJOdGd HMK ef hLhg GdHMK GdChd hgh Gdbhi efY UZQi GdbjGSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B2\ 319s
(3GdPQjYI (B6\ (3HYO (B401s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3CUhd Gdabgs